MK

\(\sqrt{2}.\sqrt{18x}-\sqrt{25x}+\sqrt{24}-\dfrac{1}{\sqrt{2}}\sqrt{8x}\) với \(x\ge0\)

GD
26 tháng 11 2023 lúc 17:12

\(\sqrt{2}.\sqrt{18x}-\sqrt{25x}+\sqrt{24}-\dfrac{1}{\sqrt{2}}.\sqrt{8x}\\ =\sqrt{2.18x}-\sqrt{25x}+\sqrt{24}-\sqrt{\dfrac{8x}{2}}\\ =\sqrt{36x}-\sqrt{25x}+\sqrt{24}-\sqrt{4x}\\ =\sqrt{6^2.x}-\sqrt{5^2x}+\sqrt{3.4^2}-\sqrt{2^2x}\\ =6\sqrt{x}-5\sqrt{x}+4\sqrt{3}-2\sqrt{x}\\ =4\sqrt{3}-\sqrt{x}\left(x\ge0\right)\)

Bình luận (0)

Các câu hỏi tương tự
KN
Xem chi tiết
1N
Xem chi tiết
KT
Xem chi tiết
LL
Xem chi tiết
H24
Xem chi tiết
NL
Xem chi tiết
NH
Xem chi tiết
H24
Xem chi tiết
TN
Xem chi tiết